UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA PADA BIDANG STUDI BIOLOGI TENTANG FOTOSINTESIS MENGGUNAKAN KOOPERATIF TIPE STAD PADA SISWA KELAS IX SMPN 1 RAMBAH TAHUN PELAJARAN 2013/2014 - Nst, Satria (Edu Research, 2014)
Problems of arising out in study of Biology, specially elementary interest oritems “it concerning the expenditure systems and nerve and role of in life" in class of IX Semester I SMPN 1 Rambah Year 2013 / 2014. Teacher with study of standard have been executed, but in so many opportunity of question and answer, class discussion, and daily restating, achievement and activity learn them very low